Revitalisasi Dakwah dalam Menghadapi Dampak Negatif Budaya Global di Indonesia - Wiryo Setiana (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2011)
The changes in various of living domain which caused by globalization, constitute da’wah challange need to anticipated professionally. The da’wah experts, both teoritist and practists musn’t stay, they must use all ability, increase their competence associate with global demmand. Among competence need to owned by da’i such as: competence in information technology, internet, LCD, Multimedia Messaging Service (MMS), and so on.